2017
DOI: 10.1177/0145721717712457
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Support on Self-care of Patients With Diabetes: What Is the Effect of Diabetes Type? Systematic Review and Meta-analysis

Abstract: Purpose This meta-analysis examined relationships between social support and self-care in type 1 (T1DM) and 2 diabetes mellitus (T2DM). Methods We searched for published and unpublished studies using the following databases: PubMed, Embase, PsycINFO, the Cochrane Library, and Medline. MeSH search terms included "diabetes mellitus," "social support," "caregiver," "self-care," "self-management," "self-care skills," and "coping behavior." Studies reporting correlations between social support and self-care were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 49 publications
7
72
3
3
Order By: Relevance
“…Studies with significant findings regarding age consistently demonstrated that young adults experienced poorer self-management behaviors. This aligns with other research, which indicates that young adults with chronic conditions may need specialized interventions in order to improve self-management behaviors (Plevinsky, Gumidyala, & Fishman, 2015;Song, Nam, Park, Shin, & Ku, 2017;Trivedi & Keefer, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Studies with significant findings regarding age consistently demonstrated that young adults experienced poorer self-management behaviors. This aligns with other research, which indicates that young adults with chronic conditions may need specialized interventions in order to improve self-management behaviors (Plevinsky, Gumidyala, & Fishman, 2015;Song, Nam, Park, Shin, & Ku, 2017;Trivedi & Keefer, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…The perceived emotional support from close others was found to be a significant predictor of diabetes self-care activity for Japanese female patients, whereas for USA patients it was not 9 . These findings are in accord with other reports from Asian countries [10][11][12][13][14] . Thus, an individual's value on interdependence with others among Japanese patients might increase psychological barriers due to concerns about potential friction, and might adversely affect their choices of diabetes self-care.…”
Section: Introductionsupporting
confidence: 93%
“…In the present project, we have defined these predictors as “dyad‐related” because they will be measured in both patients and caregivers. The results of individual studies conducted on DM, COPD and HF patients have shown that self‐care is poorer when patients and caregivers are stressed (Endrighi et al., ; Kaptein et al., ; Dionne‐Odom et al., ), are depressed (Bourbeau & Bartlett, ; Dickson et al., ; Jerant, Kravitz, Moore‐Hill, & Franks, ; Katon, ), receive poor social support (Bidwell et al., ; Graven & Grant, ; Lyons et al., ; Pereira et al., ; Song, Nam, Park, Shin, & Ku, ), do not collaborate in symptom management (Buck, Kitko, & Hupcey, ; Buck, Zambroski, & Hupcey, ) and have a lower mutuality (i.e., “the positive quality of the relationship between caregiver and care receiver”) (Lum, Lo, Hooker, & Bekelman, , p. 307).…”
Section: Introductionmentioning
confidence: 99%